Pengaruh Struktur Modal Terhadap Nilai Perusahaan dengan Ukuran dan Umur Perusahaan sebagai Variabel Moderator (Studi Kasus Tahun 2014- 2016) pada Perusahaan Sub-Sektor Makanan dan Minuman yang Terdaftar di BEI - Tunggal, Cecilia Audrey; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2018)
One stock price is determined by public trust towards a company. The public will be more trust in companies which have experiences in dealing with problems and have a lot of assets. Hence, this can minimize the possibility of companies not paying dividends to shareholders and the possibility of being bankrupt. The hypothesis is that the capital structure, firm size, and firm age, the capital structure moderated by firm size and firm age have a significant positive effect on the value of manufacturing companies focused on food and beverage. The type of research which is used is explanatory research.In this study, there is no sample and the population is taken by purposive–judgment, there are 30 data in this research. The analytical method used by using simple linear analysis, multiple linear analysis, F test, t test and interaction test. All of the analysis is done using SPSS for Windows version 24.0. The results show that the variable of DAR gave a significant positive effect and had an influence of 21.5% against firm value. The variable of DER gave a significant positive effect and had an influence of 49.2% against firm value.The firm size variable has a negative effect and am influence of 39,3% to company value. Company age variable have a positive effect and have 15.5% influence to company value. The firm size variable as a moderator variable has a negative relation to firm value. Company age variable as moderator variable have positive relation to firm value. Based on the results, it is advisable for the company to maintain the stability of capital structure by using internal and external capital sources as well as maintaining financial condition. Thus, the company can grow and survive for a long time. It is expected that the stock price as an indicator of the value of the food and beverage sub-sector will increase.